Changes in California cannabis exposures following recreational legalization and the COVID-19 pandemic. (4th May 2022) - Roth, Winter; Tam, Mitchell; Bi, Carrie; Kim, June; Lewis, Justin; Ho, Raymond; Apollonio, Dorie E.
Abstract: Introduction: Since 2012, eighteen states and the District of Columbia have legalized recreational cannabis. Past research suggests this policy change is associated with increased cannabis exposures however this has not yet been studied in California, despite its status as the world's largest legal cannabis market. Methods: This observational, retrospective study analyzed trends in cannabis exposures reported to the California Poison Control System (CPCS) from 2010 to 2020. We assessed shifts in exposures before and after the legalization of recreational cannabis in November 2016, the establishment of recreational retail sales in January 2018, and the institution of a statewide shelter-in-place order due to the COVID-19 pandemic in March 2020 using interrupted time-series analysis and reviewed all records to identify specific products associated with exposures. Results: Between 2010 and 2020 edible exposures increased from near zero to 79% of exposures in 2020. Cannabis exposures significantly increased following recreational legalization in 2016 (by an estimated 2.07 exposures per month [CI: 0.60, 3.55]; p  < 0.01) and initiation of retail sales in 2018 (0.85 [CI: 0.12, 1.58]; p  < 0.05). There was no significant change in cannabis exposures following the first shelter-in-place order of the COVID-19 pandemic (1.59 [CI: −1.61, 3.68]; p  = 0.43). Cannabis exposures for those thirteen and under increased significantly both after recreational legalization (1.04 [CI: 0.38, 1.70]) and after the opening of the retail sales market (0.73 [CI: 0.34, 1.12]), but not following the shelter-in-place order (1.59 [CI: −1.61, 3.68]), nor was there a significant change for those older than thirteen. Conclusions: Our findings suggest that cannabis legalization is linked to increased exposures, particularly for products such as gummies and candy edibles among children under the age of thirteen. Clinicians should be aware of these risks and communicate them to patients, and policymakers should consider stronger regulations on packaging to reduce these exposures. Key points: Question: How have cannabis exposures changed following legalization of recreational use, the opening of the recreational retail sales market, and the institution of shelter-in-place orders during the COVID-19 pandemic? Findings: In this retrospective review of 10, 757 cases reported to the California Poison Control System (CPCS) between 2010 and 2020, exposures increased significantly after the legalization of recreational cannabis use and the opening of the recreational retail sales market, particularly among children, who primarily consumed candies and gummies. Meaning: Stronger regulation of cannabis edibles that mimic other products is warranted to decrease exposures among children.